Investigations into un-mitigated troposphere and multipath effects on kinematic GPS for 3-dimensional monitoring of high rise buiding movements - Mohd Suldi, Azman Bin (2006)
Monitoring is a process of observing any changes on a monitored subject. Deformation monitoring is a process which consists of four stages: specification, design, implementation and analysis [Kennie et al., 1990], with the structure being monitored on a daily, hourly or continuous basis for any changes in position, size and shape. With the Global Positioning System (GPS), a 24-hour all weather monitoring system can be established. However, for kinematic GPS, un-mitigated troposphere and multipath remain as the main source of errors in the position residuals. These were investigated in detail using data from field trials conducted by the author which suite their particular purposes. The investigations were made using static and moving stations, and included stations at the same altitude, and stations with a high difference in altitude, and baseline lengths of less than ten kilometres. Using Adaptive Filtering (AF) technique, common signals in two time series can be extracted. By performing AF and interchanging position residuals time series as reference and desired (Forward and Backward) using consecutive days of data will show the multipath and this can be confirmed with a third day of data. While same day AF can be used to separate un-mitigated troposphere and movements from receiver noise. The position residuals considered in this thesis were processed with Leica Ski-Pro Version 3.0 software. These were validated and through comparisons made using a kinematic GPS processing software named KINPOS, developed by previous researchers at the IESSG, University of Nottingham and the use of Virtual Reference Station (VRS) data were also investigated by comparing with actual data. Through the field trials carried out on Snowdon, University campus, Humber Bridge and Forth Road Bridge, the novelty of this thesis is that it demonstrates that by better understanding the trends in unmitigated troposphere and multipath, the use of kinematic GPS for monitoring tall structures can be improved, making the results more suitable for engineers and building owners or managers to better assess building performance during extreme motions caused by traffic, earthquakes, strong winds, and other climatic conditions.